MODEL OF IMPLEMENTATION VIRTUAL TRADING APPLICATION TO INCREASE THE STUDENTS INTEREST ON INVESTING AS A BEGINNERS INVESTOR - Andi Runis Makkulau (Universitas Islam Balitar, 2021)
Nowadays the capital market through Indonesia Stock Exchange (IDX) is intensively conducting